KSU lean value marketing program - G L Keeler; Michael D Tokach; Jim L Nelssen; Robert D Goodband; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 1992)
The KSU Lean Value Marketing Program was developed to assist producers in understanding the quality of their market hogs by marketing on a wholesale cut basis. The program also allowed analysis of the current marketing practices of the producer in relation to sort loss. Producers lost an average of $1.08 (0 to $4.95) per head from sort loss by not marketing pigs in the proper weight range. Wholesale cuts for the 34 farms indicated that percent loins, hams, and spareribs represented the greatest portion of carcass value, whereas percent pork fat and bellies most accurately predicted the farms with low value carcasses. Backfat measurements and wholesale cut marketing indicated a large variation in genetic quality of pigs on swine farms in Kansas. The KSU Lean Value Program provides producers with important insights concerning their marketing practices and the genetic quality of pigs that they are currently producing.; Swine Day, Manhattan, KS, November 19, 1992
Keywords: Swine day; 1992; Kansas Agricultural Experiment Station contribution; no. 93-142-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 667; Swine; Marketing; G-F